HOW ACADEMIC SUPERVISION ENHANCES TEACHER PROFESSIONALISM THROUGH PERSONALITY DEVELOPMENT? - Poniman , Poniman; Desiga, Hanifa Intan; Harianto , Harianto; Pangestu, Fajar Agung (Counsenesia Indonesian Journal Of Guidance and Counseling, 2024)
This research aims to explore how academic supervision can enhance teachers' professionalism by encouraging their personal development, improving their teaching competence, and ultimately resulting in better student performance. The method used in this research is quantitative research with a descriptive quantitative survey method. The population in this study were 273 State Vocational School teachers in Lampung Province who were selected using simple random sampling. This research uses a standardized instrument by adopting and adapting the Teacher Supervision and Evaluation Survey. Analysis prerequisite tests are carried out by testing validity, reliability, normality and homogenity to ensure the validity of the instrument. Hypothesis testing in this research uses simple linear regression techniques. All research data was tested using SPSS version 26 for Windows software.Results study This shows that there isThe influence of academic supervision on the professionalism of SMKN teachers in Lampung province through personality development with a percentage of 44.8%.